Clinicians' practice environment is associated with a higher likelihood of recommending cesarean deliveries. (August 2014) - Cheng, Yvonne W.; Snowden, Jonathan M.; Handler, Stephanie; Tager, Ira B.; Hubbard, Alan; Caughey, Aaron B.
Abstract Objective: Little data exist regarding clinicians' role in the rising annual incidence rate of cesarean delivery in the US. We aimed to examine if clinicians' practice environment is associated with recommending cesarean deliveries. Study design: This is a survey study of clinicians who practice obstetrics in the US. This survey included eight clinical vignettes and 27 questions regarding clinicians' practice environment. Chi-square test and multivariable logistic regression were used for statistical comparison. Results: Of 27 675 survey links sent, 3646 clinicians received and opened the survey electronically, and 1555 (43%) participated and 1486 (94%) completed the survey. Clinicians were categorized into three groups based on eight common obstetric vignettes as: more likely (n = 215), average likelihood (n = 1099), and less likely (n = 168) to recommend cesarean. Clinician environment factors associated with a higher likelihood of recommending cesarean included Laborists/Hospitalists practice model (p < 0.001), as-needed anesthesia support (p = 0.003), and rural/suburban practice setting (p < 0.001). Conclusion: We identified factors in clinicians' environment associated with their likelihood of recommending cesarean delivery. The decision to recommend cesarean delivery is a complicated one and is likely not solely based on patient factors.